MENINGKATKAN KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN MELALUI METODE PROYEK DEKORASI DI PAUD DELIMA KECAMATAN KANDIS KABUPATEN SIAK - Lilis Suwarni; Febrianlismanto Febrianlismanto; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The research aims: 1) to know the method of decorating the project can improve the emotional intelligence of children aged 5-6 years in PAUD Delima District Kandis Siak Regency. 2) to know how to improve the emotional intelligence of children aged 5-6 years through the method of decorating projects in PAUD Delima District Kandis District Siak. 3) to know the increased emotional intelligence of children aged 5-6 years after the method of decorating project in PAUD Delima District Kandis District Siak. This type of research is class action research. The data in this research that is taken is primary data that is obtained from direct observation of child behavior during the activity, as the instrument used is 1) Data of Child's ability, 2) teacher activity Data, 3) child activity Data. The subject of research is 5-6 years old in PAUD Delima District Kandis in Siak Regency which amounted to as many as 18 children, consisting of 8 men and 10 women. Based on the results of the known research that 1) the method of decorating projects can improve the emotional intelligence of children aged 5-6 years in PAUD Delima District Kandis Siak Regency. 2) Emotional intelligence of children aged 5-6 years in Paud Delima Kandis District of Siak Regency before using the method of the design project of the to began to develop (MB). After using the method of decorating the project in cycles I and II in general the emotional intelligence of children has developed very well (BSB). 3) In the hypothesis testing can be seen the increase gained from each cycle. Where the increased emotional intelligence gained from before the action into the I cycle increased by 51.95%. While the emotional intelligence increased from cycle I to cycle II amounted to 30.71%, and overall increased emotional intelligence from the initial data to cycle II by 98.62%..Key Words: Emotional Intelligence, Decorating Project Methods